… At Least in Scotland. Issue 2 (1st April 2004) - Shah, P.; Stewart, G.; Fooks, A.R.; Pounder, D; McIntyre, P.; Nathwani, D.; White, K.
Abstract : THE STORY A right-handed conservationist in his fifties, who was also an artist and licensed bat handler, was admitted to hospital with a history of acute painless haematemesis. He also complained of severe pain in his left arm and shoulder over the preceding 7 days for which he had been taking ibuprofen without much benefit. Past medical history included pulmonary tuberculosis in childhood. He was otherwise well. There was no family history of note. He had not been abroad in the previous 7 years, and had been resident in Angus, Scotland, for 3 years, working with Scottish National Heritage. He was able to give a history of bat contact, indeed he had been bitten by a Daubenton's bat (Fig. 1) on his left hand 4 months prior to admission. He had never in the past received any anti-rabies vaccine nor had he received any post-exposure anti-rabies prophylaxis. ON EXAMINATION He